Short Communication: Updated tabular key and improved browser-based interactive key to species of Pratylenchus Filipjev (Nematoda: Pratylenchidae) - Abdul Gafur (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Gafur A. 2020. Short Communication: Updated tabular key and improved browser-based interactive key to species of Pratylenchus Filipjev (Nematoda: Pratylenchidae). Biodiversitas 21: 3780-3785.  Pratylenchus is the genus of plant-parasitic nematodes that attack many crop plants and cause significant economic losses worldwide. Attempts have been made to control the parasitic nematodes. However, incorrect identification of species has hindered biological studies on the nematodes and has led to improper and inefficient control measures. To facilitate identification of Pratylenchus species, a prototype of a cross-platform, browser-based computer-assisted identification key for species of Pratylenchus has been developed, based on the pre-existing tabular key. This paper described updates and improvements that have been made to enhance the performance of the prototype key. Updates on the tabular key, which the browser-based key was based on, were made primarily to incorporate all-new species that have been subsequently published and new data from further reports of existing species. Illustrations of characters and character states were added to the key to help users decide which character states best correspond to their specimens. Drawings of each species were also given to provide general ideas on how the species look like.  The user interface has been revised in which species name(s) relevant to selected character state(s) was listed, instead of highlighted from a lengthy full list.